Bacterioplankton from cenotes and anchialine caves of Quintana Roo, Yucatan Peninsula, Mexico - Alcocer, Javier; Lugo, Alfonso; Sánchez, María del Rosario; Escobar, Elva; Sánchez, Malinali (Revista de Biología Tropical, 1999)
The seasonal fluctuation of bacterioplankton densities were evaluated in five cenotes and two anchialine caves of Quintana Roo, northeastern Yucatan Peninsula. Bacterioplankton densities were extremely low (5.8 ± 0.35 x 102 - 8 ± 0.48 x 103 cells/ml), even for oligotrophic environments. Non seasonal differences were detected in the cenotes, however, in the caves bacterial counts were higher in the rainy season. Bacterial densities were lower in the cenotes (5.8 ± 0.35 x 102 - 4.3 ± 0.26 x 101 cells/ml), and higher in the caves (2.7 ± 0.16 x 101 - 8 ± 0.48 x 103 cells/ml). Rainwater percolation, rich in forest'soil particulate (POM) and dissolved organic (DOM) matter into the caves, seems to promote higher bacteria! densities. In addition, surface bacteria entering groundwater in the same way as POM and DOM could also be augmenting bacterial densities in the caves. Low groundwater nutrient (0.05 - 1.7 μM total P, 34.89 - 250.9 μM total N) concentrations as well as reduce bacteria! densities characterizes the cenotes and caves as ultra- to oligotrophic environments.